Writer Identity in Transition: A Narrative Study of Pakistani MA TESOL Students’ Academic Writing - Ambreen Siddique; Zainuddin, Siti Zaidah; Cheong, Huey Fen (Jurnal Arbitrer, 2025)
Writing a thesis in English as a Medium of Instruction (EMI), particularly by non-native English authors, does not merely involve overcoming linguistic difficulties but also requires negotiating academic identity. Although much of the existing research on L2 thesis writing has emphasized lexis, grammar, and genre features, limited empirical attention has been given to how postgraduate students construct their autobiographical, discoursal, and authorial selves in multilingual, postcolonial contexts such as Pakistan. After conducting a qualitative narrative inquiry with fifteen MA TESOL graduates, drawing on semi-structured interviews, written narratives, observations, and thesis Introduction chapters, this study revealed how students’ identity construction was shaped by both institutional expectations and personal agency. The results indicate that students frequently aligned with academic conventions to secure legitimacy, while at the same time attempting to assert individuality, often oscillating between cautious compliance and authorial presence. Moreover, supervisory practices and institutional gatekeeping were found to strongly influence the scope of identity options available to writers, limiting some while enabling others. Unlike prior studies that narrowly frame L2 writing as a linguistic challenge, this article combines narrative inquiry with rhetorical analysis of thesis texts in the Pakistani context. The study provides pedagogical implications for designing culturally responsive writing instruction and supervision practices.